Metodologia de priorização de investimentos em modernização de equipamentos de proteção e manobra de subestações de distribuição - Mello, Gabriel Dutra de (2017)
The continuous and reliable supply of energy becomes a necessity of modern society, therefore, it is expected that its restoration is as fast as possible in any interruptions, and that it will reach the smallest possible number of consumers. These interruptions represent high costs for the electrical utility companies, since in addition to the loss of revenue there is a need to relocate maintenance teams, possible indemnities, and possible financial compensation for inadequate service, among others. Power substations, as well as their equipment and subsystems, are an important element in the generation and consumption chain in any electrical system, and are designed to operate for several years with low outages or failures. However it is necessary to follow the life cycle of each component of a substation, as well as its performance, evaluating the failure rates, maintenance costs, impact on the system in which it is inserted, and even overcoming its technology. In this context, the present work presents a methodology for prioritizing modernization investments in distribution substations, adopting techniques to determine feeder reliability based on the logical-structural matrix, considering the total failure rates in permanent regime and rate of failure in a permanent transitory regime, as well as a multi-criteria decision-making methodology known as Analytic Hierarchy Process, to prioritize the available alternatives. Reliability indicators are adopted and the criteria of criticality are defined, taking into account the analysis of experts in the electricity sector. A case study will be presented, where it is proposed to evaluate the prioritization of medium voltage circuit breakers, installed in an energy distribution substation located in the concession area of the RGE Sul distributor. Four feeder modules are selected, with a cycle of Operation equal to 0,3s - CO - 3min - CO, i.e. only a fast reclosing